Montmorency Tart Cherry Supplementation Has Modest Effects on the Gut Microbiome and Markers of Gut Integrity and Insulin Resistance in Mice Fed Western Diet. (7th June 2021) - Kaur, Amritpal; Ojo, Babajide; Wong, Siau Yen; Alake, Sanmi; Rassi, Guadalupe Davila-El; Pastor, Madison; Lin, Dingbo; Smith, Brenda; Lucas, Edralin
Abstract: Objectives: This study investigated the dose-dependent effects of freeze-dried Montmorency tart cherry (TC) supplementation on gut health and metabolic parameters in mice fed a western diet (WD). Methods: Six-week-old male C57BL/6 mice were randomly assigned to dietary treatment groups in a 2 × 3 factorial design with diet (control [AIN-93M] or WD, 45% fat kcal and 26% sucrose kcal) and TC (0, 5, 10% wt/wt) as factors for 12 wks. At the end of dietary treatment, body composition was assessed by dual energy xray absorptiometry, and tissues were collected to evaluate metabolic parameters and markers of gut health. Cecal content was used for bacterial and short chain fatty acid analyses (SCFAs). Results: TC at the 10% dose significantly increased the abundance of the beneficial bacterial phylum, Actinobacteria, relative to the unsupplemented groups ( P = 0.018 and 0.010 vs control and WD, respectively). Relative cecal weight ( P = 0.007) and SCFAs were significantly increased ( P < 0.05) with TC supplementation (∼20% and 2-fold for relative cecal weight and SCFAs, respectively). Histological evaluation revealed reduced ileal villi height ( P = 0.0348), width ( P = 0.0042) and area ( P = 0.0132) with WD, and TC did not alter this response. Overall, the expression of genes related to gut health (i.e barrier integrity marker, mucus layer formation, and inflammatory marker), were unaffected by both WD and TC supplementation. Body weight ( P = 0.0012), fat mass ( P = 0.007), fasting blood glucose ( P = 0.001), serum total cholesterol ( P < 0.0001), triglyceride ( P = 0.002), leptin ( P = 0.0011), plasminogen activator inhibitor 1 ( P = 0.0344), and resistin ( P = 0.0012) were increased with WD, and TC had no effect on these parameters. Despite modest effects on metabolic parameters, the homeostatic model assessment of insulin resistance, HOMA-IR, a commonly used tool for assessing insulin resistance, was improved by 50% with the 5% TC ( P = 0.0003). Conclusions: TC supplementation restored some beneficial bacteria and increased SCFAs altered by WD. However, these changes in the gut did not translate to improvement in metabolic outcomes except for HOMA-IR. The mechanism by which TC improves HOMA-IR needs to be investigated in future studies. Funding Sources: Cherry Marketing Institute and the Jim and Lynn Williams Professorship.